Media and the Economic Crisis of the EU: The ‘Culturalization’ of a Systemic Crisis and Bild-Zeitung’s Framing of Greece - Yiannis Mylonas (tripleC: Communication, Capitalism & Critique, 2012)
This article critically studies the hegemonic discursive construction of the EU’s current (2012) economic crisis, as it is articulated by political and economic elites and by mass media. The study focuses on the political economy of the particular crisis and through the critical concept of reification, the study emphasizes the hegemonic naturalization of the economic crisis by the “free market” economistic ideology. The article problematizes the positioning of Greece as the “crisis epicentre” in Europe, understanding Greece as a scapegoat and as a laboratory where political strategies of capitalist restructuring of the EU are performed. Through the frame analysis of Bild-zeitung’s headlines on the coverage of crisis-struck Greece, the article discusses a) the “culturalization” of the crisis and the diversion from a structural public debate on the global economic crisis b) the disciplinary function of crisis’ publicity, related to social control and the production of new, neoliberal social subjectivities c) the alienating effect of the culturalist crisis discourses to transnational publics, resulting to the misrecognition of the ideological and structural reasons of the given crisis, the misrecognition of the effects of the crisis and crisis-politics in people’s lives, the misrecognition of popular socio-political struggles in countries worse struck by crisis politics, and the eclipse of transnational solidarity and identification to the common issues that European people in particular are facing.